Experimental demonstration of broadband reflectionless diffraction-free electromagnetic wave routing - Zhang, Youming (2017)
Wave diffraction is fundamentally difficult to overcome in the routing and interconnection of photonic signals. Although the phenomenon of reflectionless transport through sharp corners in a routing path has been realized in many previous demonstrations, wave diffraction does not allow them to transport deep-subwavelength information or sub-diffraction-limited images. Recent advances in ɛ -near-zero and anisotropic ɛ -near-infinity metamaterials have provided unique possibilities of achieving reflectionless diffraction-free electromagnetic wave routing, but their designs are fundamentally limited to narrow bandwidths, and they have not been demonstrated in reality. Here we experimentally demonstrate broadband reflectionless diffraction-free routing of electromagnetic waves through two right-angled sharp corners in a bent microwave rectangular waveguide. An image with deep-subwavelength information is transported through the bent waveguide in a broad bandwidth. This Rapid Communication supplements and extends the current studies of metamaterials with extreme permittivities and can be useful for routing and interconnection of subwavelength photonic information.